Neurofilament light chain on intensive care admission is an independent predictor of mortality in COVID-19: a prospective multicenter study - Theodor Sievert; Ingrid Didriksson; Martin Spångfors; Gisela Lilja; Kaj Blennow; Henrik Zetterberg; Attila Frigyesi; Hans Friberg (Intensive Care Medicine Experimental, 2023)
Abstract Background Neurofilament light chain (NfL), glial fibrillary acidic protein (GFAP), and total-tau protein (tau) are novel blood biomarkers of neurological injury, and may be used to predict outcomes in critical COVID-19. Methods A prospective multicentre cohort study of 117 consecutive and critically ill COVID-19 patients in six intensive care units (ICUs) in southern Sweden between May and November 2020. Serial NfL, GFAP and tau were analysed in relation to mortality, the Glasgow Outcome Scale Extended (GOSE) and the physical (PCS) and mental (MCS) components of health-related quality of life at one year. Results NfL, GFAP and tau on ICU admission predicted one-year mortality with an area under the curve (AUC) of 0.82 (95% confidence interval [CI] 0.74 $$-$$ - 0.90), 0.72 (95% CI 0.62 $$-$$ - 0.82) and 0.66 (95% CI 0.54 $$-$$ - 0.77). NfL on admission was an independent predictor of one-year mortality (p = 0.039). Low NfL and GFAP values were associated with good PCS ( $$\ge$$ ≥ 45) at one year but not with good MCS ( $$\ge$$ ≥ 45) or GOSE ( $$\ge$$ ≥ 5). Conclusions NfL on ICU admission was an independent predictor of mortality. High levels of NfL, GFAP and tau were associated with mortality but not with poor GOSE in survivors at one year. Low levels of NfL and GFAP were associated with improved physical health-related quality of life. Graphical Abstract